Ethno-religious Minorities in Bangladesh: A Historical Analysis - Islam, Arshad; Muhammad, Muenuddin (European Journal of Applied Sciences, 2022)
Bangladesh is historically a multi-ethnic, multi religious, multilingual, and pluralistic society, including Hindu, Buddhist, Sheik, Animist, and Atheist communities. After the Liberation War, it endeavoured to sustain religious, social, as well as political harmony among the people of multi religious beliefs. Using a qualitative descriptive historical approach, this study investigates the empowerment of the ethno-religious groups in Bangladesh. The paper is divided into two parts. The first part presents an overview of the current condition of ethno-religious minorities in Bangladesh, and the second explores why the ethno-religious minorities are facing multiple forms of discrimination in Bangladesh.